2012
DOI: 10.1109/jphotov.2012.2202876
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of a Single-Axis Tracking PV System

Abstract: In this paper a performance analysis of a photovoltaic (PV) tracking system is conducted, to study its efficiency based on experimental results of a specific power plant. A single-axis system is analyzed, taking into account different indexes to better characterize the overall system performance. Experimental data have been collected by an on-site monitoring system over a period of one year, bringing some final considerations and comparative results on PV-system efficiency

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…The study showed that the one-axis tracking system could intercept more irradiance than the fixed bracket system and produce 19% more energy. In 2012, Dolara et al proposed a one-axis tracking system performance analysis [15]. Their results showed that the system could effectively increase the output power of solar panels when compared to fixed systems.…”
Section: Passive Tracking Strategiesmentioning
confidence: 99%
“…The study showed that the one-axis tracking system could intercept more irradiance than the fixed bracket system and produce 19% more energy. In 2012, Dolara et al proposed a one-axis tracking system performance analysis [15]. Their results showed that the system could effectively increase the output power of solar panels when compared to fixed systems.…”
Section: Passive Tracking Strategiesmentioning
confidence: 99%
“…The high number of modules, the different radiation level over the panel area and the long distance between PV panels and converters are contributing to the overall system power losses. The complexity represents also an additional factor in maintenance and control operations, since a failure in one PV module, in most of the cases, is difficult to detect [23].…”
Section: Open Accessmentioning
confidence: 99%
“…Lazaroiu et al [19], Cruz-Peragón et al [20], and Virtuani and Fanni [21], Heslop and Macgill [22], Mousazadeh et al [23], and Dolara and Mussetta [24] performed comparative analyses on the electricity generation of the PV system according to the tracker type. In these previous studies, the performance of the electricity generation on the PV panel was found to be carried out in the order of the dual tracker, single tracker, and fixed type.…”
Section: Introductionmentioning
confidence: 99%